Kalsium Sulfat sebagai Bone Graft - Eddy Eddy (Jurnal Kedokteran Gigi Terpadu, 2021)
Calcium sulfate, which is also known as gypsum or Plaster of Paris has been used widely for more than a century. The use of calcium sulfate is not limited only to industry or food, but also to medicine and dentistry. Furthermore, calcium sulfate can be used as a bone graft for bone regeneration after tooth extraction or other bone loss cases. The development of calcium sulfate has attracted much attention from researchers due to its full biodegradability in bone defects, stimulatory effect on angiogenesis, minimal inflammatory responses, and low cost of production. This article reviews the use of calcium sulfate as a bone graft in medicine and dentistry as well as the advantages and the disadvantages.